English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

can someone please show me how to get the answer to this problem?

If f(1)= -1 and f(n+1)= [f(n)]^2 - 3, find f(4).

2007-02-04 04:55:01 · 2 answers · asked by Carley 3 in Science & Mathematics Mathematics

2 answers

so from f(1) = -1, you can find f(2) using the equation

f(1+1) = [-1]^2 - 3
f(2) = -2

then find f(3)
f(2+1) = [-2]^2 - 3
f(3) = 1

from this you can find f(4):
f(3+1) = [1]^2 - 3
f(4) = -1

you can also see the pattern of answer going -1, -2, 1, -1, ... so you can find f(5), f(6) ... without calculation

2007-02-04 05:00:09 · answer #1 · answered by Anonymous · 0 0

Figure out f(2). Then figure out f(3). Then f(4) will be easy too.

2007-02-04 12:57:59 · answer #2 · answered by Curt Monash 7 · 0 0

fedest.com, questions and answers